Highlights in Skin Cancer - Vereecken, Pierre (IntechOpen, 2013)
Highlights in Skincancer is a companion handbook published expressly for all the practitionners who are interested in skin cancers: medical oncologists and dermatologists but also residents, general practitionners, surgeons, plastic surgeons. The book is designed to teach new aspects of skincancers in the context of practical clinical settings. Each topic is an expert view of a specific skincancer field. Highlights in Skincancer provides information on a wide range of skincancer topics with emphasis on the emergence of new diagnostic approaches, therapeutic perspectives, and a better insight into the biology of the skin tumours. No doubt that the Highlights in Skincancer will be considered as a real tool throughout a medical career.